Using Homophone Game to Improve Students' Pronunciation at Junior High School 5 of Tidore Archipelago - S Syamsia; Manawia Salamat (Jurnal Langua, 2019)
This study was conducted to examine the effect of homophone game towards the students’ pronunciation improvement. Designed as a classroom action research, this study took place in the state junior high school 5 of Tidore archipelago. The researcher involved 20 students as the participants of the research. Through two cycles, the analysis of the data indicated that homophone game could improve the students’ pronunciation.